Prevention Of Hypertension Through The Use Of Moringa Leaves In The Elderly Of Kunduran Village - Miasaka Agustina; Neni Ardila; Resmini Resmini; Nailah Zhafira; Hengky Tranado (Jurnal Pengabdian Mandiri, 2026)
Hypertension is one of the most common health problems and a major risk factor for heart disease, stroke, and kidney failure. According to the results of a 2023 survey by the Indonesian Ministry of Health (Kemenkes), the prevalence of hypertension in people aged 18 years and older was recorded at 30.8%. Prevention of hypertension does not only depend on pharmacological therapy, but can also be done through non-pharmacological approaches such as diet management, physical activity, stress management, and the use of natural ingredients that have the potential to lower blood pressure. One herbal plant that has great potential in preventing hypertension is moringa leaves (Moringa oleifera). Moringa leaves are known to be rich in various nutrients and bioactive compounds, such as potassium, calcium, antioxidants, flavonoids, and polyphenols, which play a role in maintaining blood vessel health and helping to lower blood pressure. The antioxidant content in moringa leaves also serves to reduce oxidative stress, which often occurs in the elderly and contributes to the onset of hypertension. In addition to their high nutritional content, moringa leaves are easy to cultivate and can be processed in various forms, such as vegetables, herbal tea, or powder, making them practical for consumption by the elderly. The use of moringa leaves as a preventive measure against hypertension is expected to be a safe and sustainable natural solution, while also supporting community independence in maintaining health.